2018
DOI: 10.1002/ange.201810538
|View full text |Cite
|
Sign up to set email alerts
|

The p‐Orbital Delocalization of Main‐Group Metals to Boost CO2 Electroreduction

Abstract: Enhancing the p‐orbital delocalization of a Bi catalyst (termed as POD‐Bi) via layer coupling of the short inter‐layer Bi−Bi bond facilitates the adsorption of intermediate *OCHO of CO2 and thus boosts the CO2 reduction reaction (CO2RR) rate to formate. X‐ray absorption fine spectroscopy shows that the POD‐Bi catalyst has a shortened inter‐layer bond after the catalysts are electrochemically reduced in situ from original BiOCl nanosheets. The catalyst on a glassy carbon electrode exhibits a record current dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(35 citation statements)
references
References 46 publications
0
35
0
Order By: Relevance
“…lectrochemical reduction reaction of CO 2 (CO2RR) to useful products provides one practical way to deal with the urgent problems of global warming and energy crises 1,2 . Substantial effort has been devoted to searching for catalysts for such process to produce valuable products 3 , such as formic acid (HCOOH) or formate (HCOO − ) [4][5][6] .…”
mentioning
confidence: 99%
“…lectrochemical reduction reaction of CO 2 (CO2RR) to useful products provides one practical way to deal with the urgent problems of global warming and energy crises 1,2 . Substantial effort has been devoted to searching for catalysts for such process to produce valuable products 3 , such as formic acid (HCOOH) or formate (HCOO − ) [4][5][6] .…”
mentioning
confidence: 99%
“…(See Figure (d)). This difference is probably due to the reduction of BiOCl (Bi 3+ ) to metallic bismuth (Bi°) after the reduction reaction as reported earlier where it was also found that leached Cl − ions had no influence on the performance . It is thus clearly evident that the Bi (001) facets present in BiOCl is responsible for the reduction of CO 2 to formate.…”
Section: Resultsmentioning
confidence: 99%
“…2 [13,14]. More recently, the high electrocatalytic activity of bismuth for CO 2 reduction has attracted a lot of attention [15][16][17]. It highly promotes the formation of CO or formate depending on the nature of the electrolytic medium.…”
Section: Accepted Manuscriptmentioning
confidence: 99%